Grape cultivation in Himachal Pradesh is promising - Naik, Sharmistha; Somkuwar, R G; Sharma, A. K .; Sawant, S. D. (Indian Horticulture, 2019)
Vast areas of Kinnaur district of Himachal Pradesh fall under dry temperate high hills and are aptly suitable for grape cultivation. In these areas, farmers grow grapevines in their backyards, on bunds of fields and on road side. They do not apply fertilizers, agro-chemicals, pesticides and no pruning and training is followed. Simply, the grapevines are allowed to climb on field/roadside trees. Thus, grape production in Kinnaur is organic by default without much pressure on cultivable land. Due to lack of infrastructure for producing and post-production handling of wines, grapes produced in Kinnaur district are mainly used for preparing traditional fermented and distilled beverage known as Angoori. This beverage is being distilled and consumed for centuries in the area without any casualty due to liquor poisoning and as a result farmers in Kinnaur have been permitted by the Government of Himachal Pradesh to distil certain quantity of Angoori for their personal consumption. Traditional indigenous fermentation practiced in the region is low cost, less labour intensive and raw material is locally and easily available. These fermented products have a potential to grow into a small or medium size industry, if scientific, technological and infrastructural support is extended to the existing folk technologies/practices. This would also supplement Indian wine industry for diversifying its product range.